Design of a high-repetition rate photon source in a quantum key distribution system - Wang, Jian; Cui, Ke; Luo, ChunLi; Zhang, HongFei; Zhou, Lei; Chen, TengYun; Liang, Hao; Jin, Ge (Science China. Information sciences, 2013)
Photon source with high-repetition quantum message transmission is needed in the quantum key distribution （QKD） system for long distance and high-repetition rate. We design high-repetition-rate weak coherent light by applying a practical QKD system with decoy states and polarization coding including an FPGA-based true random number generator, narrow pulse shaping under the modulation of high-speed true random number as well as its laser driver. The test indicates that the repetition rate of such light can attain a high performance of 650 MHz, pulse width less than 300 ps, stability of pulse amplitude better than 5%, and extinction rate better than 1000：1.